Striking for Freedom: The 1831 Uprising at Golden Grove Plantation, Cat Island - Meyers, Allan D. (International Journal of Bahamian Studies, 2015)
Although the study of colonial Bahamian slave resistance has advanced in recent decades, key episodes of insurrection have yet to be fully explored. Recent investigation of primary source materials related to an 1831 uprising at Golden Grove, Joseph Hunter’s plantation at Cat Island, suggests that its causes and consequences were more complex than have hitherto been acknowledged. Juxtaposition of an official narrative, espoused by slave owners, with a counternarrative, by at least some slaves, emphasizes historical multi-vocality. Details of the case, which reached London at a time of accelerating abolitionism, underscore several broader themes in the history of West Indian slavery. These include the pervasive nature of resistance, the place of amelioration laws in stimulating rebellion, and the role of authoritative slaves in kin to labor strikes. The degree to which scholars stress confrontational resistance at Cat Island and other Bahamian locations has important implications for contemporary political discourse.